New Estimates for Direction of Trade Statistics - Marini, Marco (IMF Working Papers; Working Paper ;, 2018)
In March 2017, the IMF published an upgrade of its Direction of Trade Statistics (DOTS) dataset. This paper documents the new methodology that has been developed to estimate missing observations of bilateral trade statistics on a monthly basis. The new estimation procedure is founded on a benchmarking method that produces monthly estimates based on official trade statistics by partner country reported at different times and frequencies. In this paper we describe the new estimation methodology. Additional data sources have also been incorporated. We also assess the impact of the new estimates on trade measurement in DOTS at global, regional, and country-specific levels. Finally, we suggest some developments of DOTS to strenghten its relevance for IMF bilateral and multilateral surveillance.